State Variable Implementation of Stationary Reference Frame Filters for Active Filter Systems - Senini, S.; Wolfs, Peter (University of Canterbury NZ, 2003)
This paper presents a novel and elegant implementation of a synchronous reference frame filter for power system harmonic extraction. This filter does not require the sine and cosine terms normally required of SRF filters. The novelty of this approach is the use of a state variable representation to develop the filter structure. Filters based in the stationary reference frame have been presented based on classical control approaches, but these filters tend to be inelegant in their implementation. Another beauty of this approach is that a structural relationship exists between the SRF filter and its stationary frame state variable implementation, which allows the approach to be easily extended to higher order filters or controller structures.